KOMUNIKASI YANG EFEKTIF DALAM PROSES BELAJAR MENGAJAR DI SEKOLAH TINGGI MANAJEMEN INFORMATIKA DAN KOMPUTER AMIKOM PURWOKERTO - Yusmedi Nurfaizal (Pro Bisnis, 2008)
In learning process, communication occupied in a central position. Learning was a transactional communication porcess between teacher n students that involued some interlaced components. Transactional communication was a mutual gift process where both interlaced sides on a different position had same weight upon a purpose that favourabled each other. An effective communication process in lecture teaching-learning process could make possible to increase students absorbtion power, that on the turn students could get an optimal achievement. There were some thing that should be niticed to make the communication had function in levture effectivity achieving, these are 1) Teachers should be able to think and speak clearly, 2) Teachers can influence that message which will be delivered was an important thing, 3) Teachers accomplished learning purposes clearly and easy to understand by students, 4) Teachers mastered the material which was delivered to the students, 5) Teachers understood the effective communication process and applied it constantly, 6) Teachers should be able to get emphaty from students, 7) Teachers always keep eye contact, constant voice and avoided disturbed utterances, 8) Teachers created a communication plan well. Some things that should be notice by students were : 1) Students should be able to notive main things on each materials which was delivered by teachers, 2) Students needed to prepare themselves in listening and understanding the material which was delivered by teachers, 3) Students were more notice on talk contents than on the people, 4) Students should have an ability in controlling the emotion.